Peningkatan Hasil Belajar IPAS melalui Model Pembelajaran Kooperatif Tipe Jigsaw pada Siswa Kelas V SDN Putat Jaya IV Surabaya - Inka Novianti (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
This review means to further develop the learning results of 5th grade understudies of SDN Putat Jaya IV Surabaya in the subject of regular assets through the use of the Jigsaw type helpful learning model. This review utilized a Study hall Activity Exploration plan with the PTK model made by Kemmis and Mc Taggart. The stages include: (1) arranging, (2) execution, (3) perception, and (4) reflection. This homeroom activity research (PTK) was led north of two cycles, with each cycle comprising of arranging, execution, perception, and reflection stages. Student learning outcomes improved, according to the outcomes. The average student learning completion score in cycle I was 73.3 percent, while the average score in cycle II was 86.7 percent, or 78.3. Understudies' dynamic cooperation, connection, and coordinated effort during the educational experience expanded when the Jigsaw model was utilized, and this added to the accomplishment of the foreordained achievement markers